Child labour, future earnings and occupation choice: evidence from Ghana - Lambon-Quayefio, M.P.; Owoo, N.S. (International Journal of Social Economics, 2018)
Purpose The prevalence of child labour continues to feature prominently on the agenda of many sub-Saharan African countries. The problem remains critical despite existing laws and other legislative instruments that have been put in place to address the situation. The purpose of this paper is to examine a critical consequence of child labour, that is, its effect on future earnings and occupational choice. Design/methodology/approach The most recent round of the Ghana Living Standards Survey is used for this purpose. In addition to the Heckman model, the study employs propensity score and nearest neighbour matching techniques to account for the possible self-selection in engaging in child labour activities. Also, the multinomial logit model was employed to determine the choice of occupations of people who were engaged in child labour. Findings Results indicate that early labour market entry significantly reduces future earnings, possibly due to lower human capital accumulation. These results remain robust with different estimators. Additionally, results from the second objective show that child labour increases the odds of choosing low-skilled occupations. Originality/value In Ghana, the negative consequences of child labour on educational attainment have been well documented. Less, if at all, studied are the long-term consequences of child labour, particularly on future economic status.
Keywords: Earnings; Endogeneity; Child labour; Occupational choice